Creep constitutive model of strain energy density considering the whole process of creep deformation - Yuemei Li (PLoS ONE, 2025)
Aiming at the problem that the traditional creep model is difficult to reflect the characteristics of accelerated creep stage of rock, the influence of stress state on accelerated creep is fully considered, and a constitutive model which can describe viscoplastic creep is established based on strain energy density function. In order to comprehensively improve the accurate description of the three stages of rock creep, based on the traditional Nishihara model, an improved creep model is proposed by connecting a nonlinear viscoplastic element in series. The continuous medium strain energy theory is used to analyze the sudden change process of creep macroscopic mechanical behavior, and the critical strain energy density value is defined as the control parameter to predict the occurrence time of accelerated creep. At the same time, the origin software is used to introduce different creep data for fitting. The results show that the creep constitutive model can fit the rock creep test curve well and identify the parameters. It can better simulate the creep deformation characteristics of rock under different stress levels. It can accurately reflect the nonlinear creep characteristics of the whole process of rock creep. It shows that the newly established creep constitutive model has strong applicability and correctness. It provides a new creep constitutive model for future geotechnical engineering.